Uji Kesesuaian Berkas Cahaya Kolimasi pada Pesawat Sinar-X di Politeknik Al-Islam Bandung - Oktarina - Damayanti; Indra - Gunawan (Poltekkes Kemenkes Semarang, 2021)
Background : Suitability test for light collimation are tests to ensure that x-ray aircraft meet radiation safety requirements and provide precise and accurate diagnostic or diagnostic information. Suitability test for light collimation is carried out on x-ray aircraft at Al-Islam Bandung Politeknik.Methods: The research method used in quantitative experimental method. The suitability test was carried out with a collimator test tool and beam alignment test tool placed on the tape then performed an experiment using an exposure factor of 75 Kv, 200 mA and 8 mAs with FFD 100 cm.Results: Based on the tests that have been carried out, it is known that there is a discrepancy in the width of the collimation beam. The large discrepancy between the light field area and the radiation field area, that is, the edge X₁ 0.3 cm, the edge X₂ 0.5 cm, the edge Y₁ 0.5 cm, the edge Y₂ 0.1 cm. So the value of ∆X is 0.8% FFD, the value of ∆Y is 0.6% FFD, and the value of ∆X + ∆Y is 1.4% FFD. While the deviation of the central point is less or right than 3⁰. These results indicate that the discrepancy in the width of the light beam collimation and center point deviations is still within the tolerance limits.Conclusions: There is a discrepancy between the X-ray light field and the collimated light field, but it is still within the limit of the test value to the passing value of the predefined test.